ANALISIS KUALITAS MANAJEMEN PADA PELAYANAN PUBLIK DALAM PEMBUATAN SIM DI POLRES MANDAILING NATAL - Fithrah Dwi Ananda; Muhammad Irwan Padli Nasution; Muhammad Ikhsan Harahap (ITB AAS Indonesia Surakarta, 2023)
This research is a study that analyzes how the quality of management in public services in making a Driver's License (SIM) at the Mandailing Natal Police Station. Effective and quality public services are a factor for meeting the needs of the community, especially building public trust in an institution or government agency. This research uses qualitative research methods with a case study approach. Data was collected through interviews with related parties, selection of interview data using purposive sampling techniques. In addition, researchers made direct observations in order to obtain more in-depth information about the process of making a driver's license. Based on the results of the analysis that has been conducted by researchers, the quality of management in public services at the Mandailing Natal Police Station is quite good even though it has a weakness. The lack of technology in making a SIM is very complained by the public, people hope that making a SIM can be made easier online. Based on the results of the study, the Mandailing Natal Police need to improve training and coaching for officers by updating the driver's license manufacturing process and using more effectiveness from the technology provided.